INFLUENCE OF LIPO CHITO OLIGOSACCHARIDES ON GERMINATION OF MAIZE UNDER DIFFERENT LEVELS OF SALINITY - D.UDHAYA NANDHINI; E. SOMASUNDARAM; M. MOHAMED AMANULLAH (The Bioscan, 2015)
Laboratory experiment was conducted to study the effectiveness of nod factors (LipoChito Oligosaccharides) on seed germination in maize under different levels of salinity (0, 2,4,6,8 and 10 dSm-1).Seeds were treated with nod factors and sown in petriplates. Significant reduction in the germination percentage (31 %), shoot length (3.65 cm), root length (1.2 cm), seedling vigour index (154) and salt tolerance index (4.9) was observed under thenon primed seeds of maize at increasing salinity levels. The higher reduction was recorded under 10 dSm-1. LCO primed seeds relatively increased seed germination (96 %), rootlength (13.97 cm), shoot length (23.2 cm), seedling vigour index (3570) and exhibited salt tolerance as compared to non primed seeds irrespective of thesalinity levels.The regression analysis under salt stress condition showed that aforesaid traitsall together contributed69.4 per cent for salt tolerance.The results indicated that salt stress can reduce the germinable characters suggesting that LCO (nod factors) canincrease the initial seedling growth by invigorating the salt tolerance.